Sex differences in heart rate responses to script-driven imagery soon after trauma and risk of posttraumatic stress disorder - Kleim, Birgit (2010)
OBJECTIVE: Trauma survivors’ physiological responses to idiosyncratic trauma reminders may be predictive of later posttraumatic stress disorder (PTSD). The majority of previous studies have been cross-sectional and have produced mixed findings. Sex differences may contribute to this heterogeneity. The present study investigated the predictive validity of heightened physiological responsivity to script-driven imagery and sex for the development of PTSD. METHODS: Heart rate (HR) and respiratory sinus arrhythmia (RSA) were measured at two weeks post-trauma in 158 assault survivors during baseline and while listening to an idiosyncratic trauma script. At 6 months, 15.2% of male and 28.1 % of female participants met diagnostic criteria for PTSD. RESULTS: GLM and logistic regression analyses showed that HR response to script-driven imagery and sex interacted in predicting PTSD symptom severity at six months. Women had greater PTSD symptom severities overall. Female HR responders to script driven imagery showed the highest PTSD symptom severities, and were almost three times more likely to develop PTSD at six months compared to men and female nonresponders (OR = 2.72, 95% CI= 1.13-6.57). RSA responder type did not predict PTSD, OR = .64, 95%CI = .30 – 1.33. CONCLUSION: Female trauma survivors who respond to trauma reminders with increased HR may be at particular risk of developing PTSD. Physiological reactivity to trauma cues may be a useful index for screening and prevention of PTSD.